Determinants of Achieving Early Blood Pressure Control with Monotherapy in a Primary Care Setting. Issue 9 (16th July 2013) - Stewart, Simon; Carrington, Melinda J.; Swemmer, Carla H.; Kurstjens, Nicol P.; Brown, Alex; Burrell, Louise M.; Nelson, Mark; Stocks, Nigel P.; Jennings, Garry L.; ,
Abstract : This study sought to identify the determinants of early blood pressure (BP) control associated with monotherapy in hypertensive individuals being managed in the primary care setting. The Valsartan Intensified Primary Care Reduction of Blood Pressure (VIPER‐BP) study, was a multicenter, randomized controlled trial of an intensive approach to BP management. During a standardized run‐in, 2185 participants commenced monotherapy (valsartan 80 mg/d) for 14 to 28 days. A total of 1978 participants aged 59±12 years (60% men) completed the run‐in phase. Of these, 15.1%, 43.5%, and 41.4% participants had an initial BP target of ≤125/75, 130/80, and 140/90 mm Hg, respectively. A total of 416 of 2185 participants (19.0%) subsequently achieved their individual BP target during run‐in with a mean BP change of −22.6±12.1/−12.9±8.2 mm Hg vs −4.2±16.2/−3.0±9.6 mm Hg for the rest ( P <.001). These early responders were more likely to be women (adjusted odds ratio, 1.41; 95% confidence interval, 1.10–1.80), had lower BP at baseline, were less likely to have been treated previously (or for less time), and had a less stringent BP target. An initial period of monotherapy achieved BP control in a high proportion of hypertensive individuals with key groups (including women and de novo cases) more likely to show an early BP response.